Elucidating information processing in primate basal ganglia circuitry: a novel technique for pathway-selective ablation mediated by immunotoxin - Takada, Masahiko; Inoue, Ken-ichi; Koketsu, Daisuke; Kato, Shigeki; Kobayashi, Kazuto; Nambu, Atsushi (Frontiers in Neural Circuits, 2013)
Employing a neuron-specific retrograde gene-transfer vector (NeuRet vector), we have recently developed a novel technique that achieves pathway-selective ablation in the primate brain. This technique is mediated by immunotoxin (IT) and eliminates a neuronal population that constitutes a particular pathway, leaving other pathways intact. By means of this technique, we have made an attempt to remove the hyperdirect pathway selectively from basal ganglia circuitry. The hyperdirect pathway links the motor cortex to the subthalamic nucleus (STN) directly and plays a crucial role in motor control. After electrical stimulation in the motor cortex, triphasic responses consisting of an early excitation, an inhibition, and a late excitation are usually elicited in the internal pallidal segment (GPi). Several pieces of pharmacophysiological evidence imply that the early excitation may be derived from the hyperdirect pathway. In our experiments, the NeuRet vector expressing human interleukin-2 receptor α-subunit was injected into the STN of macaque monkeys. Then, IT injections were performed into the supplementary motor area (SMA). When single neuron activity in the GPi was recorded in response to the SMA stimulation, it was found that the early excitation was significantly reduced with neither the inhibition nor the late excitation affected. The spontaneous firing rate and pattern of GPi neurons remained to be altered. This clearly indicates that IT-mediated tract targeting successfully eliminated the hyperdirect pathway with spontaneous activity of STN neurons unaffected. The electrophysiological findings were histologically confirmed by retrograde and anterograde neuronal labeling. The overall data define that the motor cortically-driven early excitation in GPi neurons is conveyed through the hyperdirect pathway. The IT-mediated pathway-selective ablation technique will provide a powerful tool for elucidating information processing in various neural networks.